We are all green: do military experiences and involvement in the criminal justice system vary across race and ethnicity among incarcerated veterans? - Peck, Jennifer H. (Deviant behavior, 2024)
Although participation in the military impacts the lives of all who serve, little research has examined how specific military experiences and criminal justice outcomes vary for veterans of color compared to Whites. The present study examines the relationship between service elements and criminal justice involvement for incarcerated veterans of different racial/ethnic backgrounds. We examine how multiple service experiences (e.g. age of entry, length of service, discharge status, etc.) are associated with arrest frequencies and types of offenses among White, Black, and Hispanic U.S. incarcerated male veterans. Using data from a nationally representative sample of individuals incarcerated in state prisons, results demonstrate that race/ethnicity was not directly related to criminal justice outcomes, but different forms of military experiences were associated with involvement in the system uniquely across racial/ethnic groups. The findings provide greater insight into the connection between military service and police/court outcomes for veterans who are justice-involved.